ANALISIS EKSPOR KOPI INDONESIA - Yodi Oskar Prada; Miksalmina Miksalmina; Apridar Apridar; Zulkifli Zulkifli (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
AbstractCoffee is one of the commodities which contribute in foreign exchange for Indonesia. As the largest coffee producing and exporting country in the world, analyzing the coffee export is important to conduct. The objective of this study is to analyze coffee exports in Indonesia. The variables used are the exchange rate, world coffee prices, and world economic growth. The data used is time series data using data from 1990-2019. The model used in this study is Multiple Data Regression with Ordinary Least Square. The data sources are from the Food and Agriculture Organization (FAO) and the World Bank (World Bank). Of the three variables used in this study, only the exchange rate variable has a significant effect on coffee exports in Indonesia, while the coffee price variable and world economic growth have no significant effect. Therefore, it is recommended to the government to maintain the stability of the Indonesian Rupiah against the US Dollar so that Indonesian coffee exports can continue to increase Keywords: Exchange Rate, Economic Growth, Indonesian Coffee Prices, Coffee Exports